Co/MoS2 nanocomposite for passive Q-switched pulse operation in erbium-doped fiber lasers - Ahmed, Hira; Asghar, Mamoon; Hameed, Hafsa; Ahmed, Rizwan; Khalil, Adnan; Iqbal, Javeed; Alrebdi, Tahani A; Asghar, Haroon (Optical materials express, 2024)
In this study, we examine the effectiveness of cobalt molybdenum disulfide (Co/MoS2) nanocomposite as a saturable-absorber for pulse generation in erbium-doped fiber lasers (EDFLs). A small amount of Co/MoS2 nanocomposite deposited on the fiber facet is implemented into the EDFL cavity to facilitate a Q-switching mechanism. The measured results show that the EDFL, emitted at 1568.13 nm, with a significant reduction in pulse duration from 26 µs to 4.7 µs and an increased repetition rate from 16.49 kHz to 83 kHz, as pump power tuned from 30.8 mW to 304.48 mW. The highest output power of 8.39 mW is further achieved, including a peak power of 17.59 mW and a maximum pulse energy of 109.93 nJ. A maximum single-to-noise ratio (SNR) of 52 dB is revealed at a pump of 249.48 mW. We further provide a comprehensive analysis of the EDFL's stability for a maximum of 6 hrs. Additionally, the Q-switched pulse operation was studied using a theoretical model subject to the nonlinear Schrödinger equation (NSE), and a reasonable agreement was found with experimental findings. This study highlights the feasibility of employing nanocomposite-based saturable absorbers in producing high-quality laser pulses, demonstrating its considerable promise for various pulsed laser applications.